(untitled) (Sustainability in Debate, 2014)
RESENHA de: Robert K. Musil. Rachel Carson and her sisters: extraordinary women who have shaped America´s environment. New Brunswick, New Jersey; London: Rutgers University Press, 2014. 309 p. ISBN 9780813562438. Fotografias, bibliografia, notas.